2012
DOI: 10.3928/01477447-20120621-34
|View full text |Cite
|
Sign up to set email alerts
|

Intra-articular Tenosynovial Giant Cell Tumor Arising From the Posterior Cruciate Ligament

Abstract: Tenosynovial giant cell tumors originate from the synovial tissue of the joints, tendon sheaths, mucosal bursas, and fibrous tissues adjacent to tendons. The disease presents in localized and diffused forms. Large joints, such as the knee, are not frequently affected. Magnetic resonance imaging has been reported to be the best noninvasive technique to diagnose these tumors. Magnetic resonance imaging diagnosis has to be confirmed by histopathological examination. Few reports exist of tenosynovial giant cell tu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 10 publications
0
8
0
1
Order By: Relevance
“…[3] The tumors are usually found on the tendon sheaths of the hands and feet and are extremely rare in the knee. [4,5,10] To date, several cases of GCTTS originating in the ACL, [6] PCL, [7] patellar tendon, [8] and medial plica [9] have been reported in the literature. In this study, we present a case of GCTTS originating from the ligamentum mucosum, which, to our knowledge, has not been previously reported.…”
Section: Discussionmentioning
confidence: 99%
“…[3] The tumors are usually found on the tendon sheaths of the hands and feet and are extremely rare in the knee. [4,5,10] To date, several cases of GCTTS originating in the ACL, [6] PCL, [7] patellar tendon, [8] and medial plica [9] have been reported in the literature. In this study, we present a case of GCTTS originating from the ligamentum mucosum, which, to our knowledge, has not been previously reported.…”
Section: Discussionmentioning
confidence: 99%
“…A few reports of tenosynovial giant cell tumour arising from PCL have also been published [9,10,11].…”
Section: Discussion:-mentioning
confidence: 99%
“…14 A few reports of tenosynovial giant cell tumour arising from posterior cruciate ligament (PCL) have also been published. 2,15,16 Kim et al 2 reported a case of 28-year-old man with 5-year history of left knee pain with an intra-articular giant cell tumour attached to the PCL. Magnetic resonance imaging revealed a regular contoured mass arising from the PCL.…”
Section: Discussionmentioning
confidence: 99%